Balleans and G-spaces - Petrenko, O.V.; Protasov, I.V. (Український математичний журнал, 2012)
We show that every ballean (equivalently, coarse structure) on a set X can be determined by some group G of permutations of X and some group ideal I on G. We refine this characterization for some basic classes of balleans (metrizable, cellular, graph, locally finite, and uniformly locally finite). Then we show that a free ultrafilter U on ω is a T -point with respect to the class of all metrizable locally finite balleans on ω if and only if U is a Q-point. The paper is concluded with a list of open questions. Доведено, що кожен болеан (еквiвалентно, груба структура) на множинi X може бути визначений деякою групою пiдстановок G множини X та деяким груповим iдеалом I на G. Цю характеризацiю уточнено для деяких основних класiв болеанiв: метризовних, стiльникових, графових, локально скiнченних, рiвномiрно локально скiнченних. Далi ми доводимо, що вiльний ультрафiльтр U на ω є T-точкою вiдносно класу метризовних локально скiнченних болеанiв на ω тодi i тiльки тодi, коли U є Q-точкою. Насамкiнець наведено список вiдкритих проблем.